Gene splicing of an invertebrate beta subunit (LCavβ) in the N-terminal and HOOK domains and its regulation of LCav1 and LCav2 calcium channels. - Taylor F Dawson; Adrienne N Boone; Adriano Senatore; Joshua Piticaru; Shano Thiyagalingam; Daniel Jackson; Angus Davison; J David Spafford (PLoS ONE)
The accessory beta subunit (Ca(v)β) of calcium channels first appear in the same genome as Ca(v)1 L-type calcium channels in single-celled coanoflagellates. The complexity of this relationship expanded in vertebrates to include four different possible Ca(v)β subunits (β1, β2, β3, β4) which associate with four Ca(v)1 channel isoforms (Ca(v)1.1 to Ca(v)1.4) and three Ca(v)2 channel isoforms (Ca(v)2.1 to Ca(v)2.3). Here we assess the fundamentally-shared features of the Ca(v)β subunit in an invertebrate model (pond snail Lymnaea stagnalis) that bears only three homologous genes: (LCa(v)1, LCa(v)2, and LCa(v)β). Invertebrate Ca(v)β subunits (in flatworms, snails, squid and honeybees) slow the inactivation kinetics of Ca(v)2 channels, and they do so with variable N-termini and lacking the canonical palmitoylation residues of the vertebrate β2a subunit. Alternative splicing of exon 7 of the HOOK domain is a primary determinant of a slow inactivation kinetics imparted by the invertebrate LCa(v)β subunit. LCa(v)β will also slow the inactivation kinetics of LCa(v)3 T-type channels, but this is likely not physiologically relevant in vivo. Variable N-termini have little influence on the voltage-dependent inactivation kinetics of differing invertebrate Ca(v)β subunits, but the expression pattern of N-terminal splice isoforms appears to be highly tissue specific. Molluscan LCa(v)β subunits have an N-terminal "A" isoform (coded by exons: 1a and 1b) that structurally resembles the muscle specific variant of vertebrate β1a subunit, and has a broad mRNA expression profile in brain, heart, muscle and glands. A more variable "B" N-terminus (exon 2) in the exon position of mammalian β3 and has a more brain-centric mRNA expression pattern. Lastly, we suggest that the facilitation of closed-state inactivation (e.g. observed in Ca(v)2.2 and Ca(v)β3 subunit combinations) is a specialization in vertebrates, because neither snail subunit (LCa(v)2 nor LCa(v)β) appears to be compatible with this observed property.